Star Formation Regions and Magnetohydrodynamic Turbulence Connection - Santos, Lucas Barreto Mota dos (2019)
Stars are known to form inside molecular clouds, out of gravitational collapse. On the other hand, the formation and maintenance of these interstellar structures is believed to be driven by turbulent motions of the magnetized fluid inside these clouds. In this work we explore, by means of three-dimensional (3D) numerical simulations and different statistical methods, including PDF (Probability Density Function), PRS (Projected Rayleigh Statistics), and power-spectrum analyses, how magnetohydrodynamical (MHD) turbulence is connected to the formation of star forming regions. We drive turbulence in an initially homogeneous isothermal environment permeated by uniform magnetic field, considering different regimes that go from transonic to supersonic, and sub-Alfvénic to super-Alfvénic turbulence. We consider two main families of models, one without self-gravity and the other including self-gravity in the gas in order to explore the collapse of structures into the molecular cloud domain. Our main results can be summarized as follows: (i) There is a clear correlation between the gradients of density (and column density) with the magnetic field orientation for sub-Alfvénic systems with and without self-gravity, with less dense regions appearing more aligned to the magnetic field and denser regions appearing more perpendicular to magnetic field. This difference is enhanced for higher sonic Mach numbers, which cause more fragmentation of the clouds; (ii) Super-Alfvénic models without self-gravity show structures mostly aligned to the magnetic field, due to dominance of the compression effects, with no important dependence with the sonic Mach number; (iii) In sub-Alfvénic models, the direction of the line-of-sight (LOS) of the integrated column density is found to influence the distribution of the projected component of the magnetic field on the plane of the sky (B perp ). This shows less coherence when the LOS is parallel to the initial magnetic field. Still, less dense regions appear predominantly parallel to B perp and denser regions appear more perpendicular to it, specially when self-gravity is considered; (iv) For the super-Alfvénic models, column density structures also appear mostly aligned to B perp and maps yield very similar behaviour for different LOS (i.e., parallel, perpendicular, or making an angle of 45º with the initial field); (v) The introduction of self-gravity enhances the formation of dense structures perpendicular to the magnetic field (as gravitational forces enforce the collapse of matter more easily along the lines), mainly in sub-Alfvénic models. This effect in super-Alfvénic models only becomes more pronounced for high sonic Mach numbers; (vi) The comparison of the results obtained from our models with observations by Planck, Herschel and BLASTPol, indicates that our sub-Alfvénic models can qualitatively better reproduce the characteristics of observed clouds. Not only the behaviour of the observed PRS, but also the general coherence of the projected magnetic field B perp is compatible with our sub-Alfvénic models for most clouds. There are clouds where twists of B perp could be explained with effects related to the direction of the LOS. Clouds like Aquila, for instance, can be well represented by models with no self-gravity or in earlier stages of collapse, while Taurus and Vela C have some similarities with models at a more advanced stage of gravitational collapse.